OP21 Predictive value of Milan Ultrasound Criteria in Ulcerative Colitis: A prospective observational cohort study. (27th May 2021) - Allocca, M; Dell'Avalle, C; Furfaro, F; Craviotto, V; Zilli, A; D'Amico, F; Peyrin-Biroulet, L; Fiorino, G; Danese, S
Abstract: Background: Endoscopic remission is associated with better outcomes in ulcerative colitis (UC). However, colonoscopy (CS) is invasive and poorly tolerated by patients. Recently, we developed and externally validated non-invasive ultrasonography based criteria [Milan ultrasound criteria (MUC)] to assess and grade endoscopic activity in UC. We also confirmed that a MUC score > 6.2 is a valid cut-off to discriminate endoscopic activity, defined by a Mayo endoscopic subscore > 2. Aim of this study was to assess the predictive role of MUC on disease course in a prospective cohort of UC patients. Methods: UC consecutive patients were followed for at least 12 months after performing baseline bowel US. UC-related outcomes, including need of treatment escalation (defined as the need of corticosteroids or change/optimization of immunosuppressants), hospitalization and surgery, were assessed at 1 year by logistic regression analysis, and were analyzed after long term follow-up (5 years) using Kaplan-Meier survival analysis. Fig. 1A and 1B. Kaplan–Meier curves for the cumulative probability of hospitalization and surgery in patients with Milan ultrasound criteria (MUC) < 6.2 (solid line) or MUC > 6.2 (dotted line). (p= 0.046; p= 0.023; respectively). Fig. 1C and 1D. Kaplan–Meier curves for the cumulative probability of hospitalization and surgery in patients with Mayo endoscopic subscore 0–1 (solid line) or 2–3 (dotted line). (p= 0.035; p= 0.071; respectively). Results: 87 UC consecutive patients were included in the study, 31 (36%) were in endoscopic remission (Mayo endoscopic subscore 0–1) and 56 (64%) in endoscopic activity (Mayo endoscopic subscore 2–3). MUC and Mayo endoscopic subscore significantly correlated at baseline (Spearman's rank correlations [rho]= 0.642; 95% confidence interval (CI) 0.499 to 0.751; p < 0.001). The multivariable analysis identified as independent predictors of need of treatment escalation throughout the 12-month period as being: MUC > 6.2 (OR: 5.95, 95% CI: 1.32–26.76, p < 0.020) and a partial Mayo score (PMS) > 2 (OR: 26.88, 95% CI: 5.01–144.07, p < 0.001). Kaplan-Meier survival analysis of long-term follow up demonstrated a lower cumulative probability of need for surgery and hospitalization in patients with MUC < 6.2 compared to MUC > 6.2 (Fig. 1 A and 1 B), as well as in patients with a Mayo endoscopic subscore of < 1 compared to Mayo endoscopic subscore of 2–3 (Fig. 1 C and 1 D). Conclusion: MUC is a novel non invasive tool that predicts the course of UC in the short and long term follow-up.